Effects of sleepiness on clinical decision making among paramedic students: a simulated night shift study. Issue 1 (16th February 2021) - Bartlett, Danielle; Hansen, Sara; Cruickshank, Travis; Rankin, Timothy; Zaenker, Pauline; Mazzucchelli, Gavin; Gaston, Matthew; Du Plooy, Dirk; Minhaj, Zahed; Errey, William; Rumble, Tyron; Hay, Taylor; et al.
Abstract : Objective: Paramedics are at the forefront of emergency healthcare. Quick and careful decision making is required to effectively care for their patients; however, excessive sleepiness has the potential to impact on clinical decision making. Studies investigating the effects of night shift work on sleepiness, cognitive function and clinical performance in the prehospital setting are limited. Here, we aimed to determine the extent to which sleepiness is experienced over the course of a simulation-based 13-hour night shift and how this impacts on clinical performance and reaction time. Methods: Twenty-four second year paramedic students undertook a 13-hour night shift simulation study in August 2017. The study consisted of 10 real-to-life clinical scenarios. Sleepiness, perceived workload and motivation were self-reported, and clinical performance graded for each scenario. Reaction time, visual attention and task switching were also evaluated following each block of two scenarios. Results: The accuracy of participants' clinical decision making declined significantly over the 13-hour night shift simulation. This was accompanied by an increase in sleepiness and a steady decline in motivation. Participants performed significantly better on the cognitive flexibility task across the duration of the simulated night shift and no changes were observed on the reaction time task. Perceived workload varied across the course of the night. Conclusion: Overall, increased sleepiness and decreased clinical decision making were noted towards the end of the 13-hour simulated night shift. It is unclear the extent to which these results are reflective of practising paramedics who have endured several years of night shift work, however, this could have serious implications for patient outcomes and warrants further investigation.